Adoption and use of electronic meeting systems to support task-oriented collaboration in large organizations in Australia and New Zealand - Pervan, Graham; Lewis, F. (Springer, 2004)
With trends towards globalization and increased competition, firms arebecoming increasingly dependent upon group work. The recent surge ofreengineering efforts to reinforce a process view of organizational work andthe emergence of virtual corporations spanning across the globe indicate thatfirms are relying more on group work today than ever before. Informationtechnology (IT) may have the capability to greatly enhance the quality of collaboration in accomplishing group tasks. This paper focuses on Electronic Meeting Systems (EMS) and empirically assesses their adoption and use in supporting task-oriented collaborative work in Australian and New Zealand organizations. Preliminary analysis of survey data collected from one hundred and forty-seven organizations indicates that EMS adoption has been somewhat limited. Barriers to adoption are identified along with implications for future research. Overall, the findings are fairly similar to the US study on which the survey instrument was based.